Comparison of MIMO based on high capacity LPWAN technology TurMassTM and LoRa - Hao JIANG; Hongming CHEN; Yilong CAO; Haoyang CUI (物联网学报)
With the rapid development of low power wide area network (LPWAN) technologies, more and more IoT terminals need to access the network.In order to deal with the challenge of massive random access, grant-free random access with massive MIMO (MGFRA) was proposed for LPWAN scenarios.The MGFRA was introduced and the performance of MGFRA to validate its performance advantage of greatly improving the channel access capacity with extreme low signaling overhead was theoretically analyzed.Further, TurMassTMwas introduced, which is a high-capacity LPWAN technology based on MGFRA.To demonstrate the advantages of TurMassTMin practical applications, TurMassTMand LoRa in signal coverage, communication rate, network capacity, low power consumption and low cost in typical LPWAN communication scenarios were compared.The comparison results show that TurMassTMhas outstanding advantages in signal coverage, communication rate, network capacity, low power consumption and low cost compared with LoRa.